Acaricidal effect of sulfuryl fluoride - Romanko, V.; Dudynska, A. (Scientific Progress & Innovations, 2025)
The study is devoted to the search for alternatives to phosphine, to which some pests have developed resistance, as well as methyl bromide, the use of which has been restricted by the Montreal Protocol. The article presents the results of studies on the effectiveness of sulfuryl fluoride against the mobile stages of mites. The study aimed to investigate the toxic effect of sulfuryl fluoride at different temperatures on the mobile stages of mites of the genera Acarus and Tyrophagus under parameters acceptable for industrial fumigation. The research objects were the mobile stages of acarid mites. The research material was sulfuryl fluoride. The following methods were used: analytical review of the topic; analysis of the biological characteristics of acarid mites; experimental – variation of different fumigation parameters (temperature, concentration, exposure duration, c (concentration) × t (time) products (CT-products), mathematical and statistical analysis using computer modeling. The results of the studies showed the toxic effect of sulfuryl fluoride against the mobile stages of Acarus and Tyrophagus mites, depending on the fumigation parameters. Lethal dose (LD) values for the mobile stages of mites were established. At a temperature of 15–22 °C, the lethal norms for sulfuryl fluoride were CT-products 1398.80 g-hr., average concentration – 21.19 g/m3, fumigation duration 66 hours. At a temperature of 23–24 °C, lethal norms were at the level of CT-products 1206.00 g-hr., the average concentration was 28.71 g/m3, and the duration of fumigation was 42 hours. At a temperature of 25–26 °C, lethal norms of sulfuryl fluoride for mites were at the following fumigation parameters: CT-products 1107.55 g-hr., average concentration 30.77 g/m3, fumigation duration 36 hours. At a temperature of 27–28 °C, lethal norms were at the level of CT-products 1005.00 g-hr., average concentration – 33.50 g/m3, fumigation duration 30 hours. At a temperature of 32 °C and above, the lethal norms for sulfuryl fluoride were CT-products 906.55 g-hr., average concentration – 34.87 g/m3, fumigation duration 26 hours. Lethal norms for sulfuryl fluoride at different temperatures were established, which are optimal for ensuring 100 % mortality of mobile stages of acarid mites, as they slightly exceed the sublethal threshold. The dependence of the fumigant’s effectiveness on temperature was observed. As the temperature decreases, the toxic load must increase to ensure 100 % mortality mites, and vice versa. The results obtained indicate the need for further research, particularly to determine optimal intervals for repeated fumigations.